(Arthur C Clarke we still need you). Trying to predict the future of the Bodleian Law Library - Bird, R (Cambridge University Press, 2008)
Ruth Bird considers how the facilities and services at the Bodleian Law Library will evolve in the 21st Century given its status as a member library of the Copyright Deposit Scheme, which means that whilst other libraries are shrinking their paper collections, it is still expanding them.